2017
DOI: 10.1002/biot.201600547
|View full text |Cite
|
Sign up to set email alerts
|

Physiological capacities decline during induced bioprocesses leading to substrate accumulation

Abstract: During the cultivation of E. coli for recombinant protein production, substrate accumulation is often observed in induction phase. Uncontrolled substrate accumulation leads to difficulties in transferring or scaling processes and even to failed batches. The phenomenon of metabolite/substrate accumulation occurs as a result of exceeding the physiological capacity to metabolize substrate (q ). In contrast to the common understanding of q as "static" value, we hypothesize that q essentially has a dynamic nature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The interruption of feeding and overfeeding was assumed to be classic technical failures that occur in the late or final stages of the induction phase. Especially, overfeeding is usually a problem with increasing induction times, because cellular performance is usually decreasing over time [32]. When no automated closed-loop feed addition is performed, substrate overfeeding is usually present, as the specific substrate uptake rate of E. coli decreases [32].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interruption of feeding and overfeeding was assumed to be classic technical failures that occur in the late or final stages of the induction phase. Especially, overfeeding is usually a problem with increasing induction times, because cellular performance is usually decreasing over time [32]. When no automated closed-loop feed addition is performed, substrate overfeeding is usually present, as the specific substrate uptake rate of E. coli decreases [32].…”
Section: Methodsmentioning
confidence: 99%
“…Especially, overfeeding is usually a problem with increasing induction times, because cellular performance is usually decreasing over time [32]. When no automated closed-loop feed addition is performed, substrate overfeeding is usually present, as the specific substrate uptake rate of E. coli decreases [32]. Therefore, the technical failures in C9 and C10 were introduced at the usual end of the induction time.…”
Section: Methodsmentioning
confidence: 99%
“…Knowledge about the state of IB QAs during a cultivation process is therefore of utmost importance. Three IB QAs are generally of importance: bead size, titer and purity, as those three quality attributes were already defined elsewhere [ 21 , 30 , 33 , 34 ]. It has been reported that inclusion body sizes can be measured with different methods, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of single process parameters like pH on IB QAs has already been investigated in literature [ 36 , 37 ]. Reichelt et al [ 34 ] showed that alterations of (q s,glu ) influence the behavior of common IB-processes, using IPTG as an inducer. The impact of the feeding rate onto product formation in E. coli BL21(DE3) has been investigated recently, though lactose was used as inducer instead of IPTG [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown within this study, that the physiological feeding rate in E. coli is highly dependent onto process parameters and consists of a rather “dynamic nature”. Physiological capacities decline during induced bioprocesses leading to substrate accumulation [35].…”
Section: Introductionmentioning
confidence: 99%